2023
DOI: 10.1109/tnsre.2023.3249831
|View full text |Cite
|
Sign up to set email alerts
|

A Cross-Space CNN With Customized Characteristics for Motor Imagery EEG Classification

Abstract: The classification of motor imagery-electroencephalogram (MI-EEG) based brain-computer interface (BCI) can be used to decode neurological activities, which has been widely applied in the control of external devices. However, two factors still hinder the improvement of classification accuracy and robustness, especially in multi-class tasks. First, existing algorithms are based on a single space (measuring or source space). They suffer from the holistic low spatial resolution of the measuring space or the locall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(2 citation statements)
references
References 54 publications
(61 reference statements)
0
2
0
Order By: Relevance
“…Many studies have shown that personalized approaches can effectively mitigate the negative effects of individual differences on MI-BCI performance. Based on the differences in the work, these studies are divided into two categories: the personalization paradigm [43][44][45][46] and the personalization algorithm [47][48][49][50].…”
Section: Relevant Research On Personalized Bcismentioning
confidence: 99%
“…Many studies have shown that personalized approaches can effectively mitigate the negative effects of individual differences on MI-BCI performance. Based on the differences in the work, these studies are divided into two categories: the personalization paradigm [43][44][45][46] and the personalization algorithm [47][48][49][50].…”
Section: Relevant Research On Personalized Bcismentioning
confidence: 99%
“…By incorporating a channel attention mechanism, more discriminative features were extracted, leading to 74% average accuracy on four class data. Moreover, Hu et al ( 2023 ) employed band common spatial pattern coupled with duplex mean-shift clustering to extract diverse features across temporal, spectral and spatial domains. By combining these with CNN, features from different domains were consolidated, significantly improving the classification results.…”
Section: Related Workmentioning
confidence: 99%